Kajian Yuridis Terhadap Pemulihan Hak Politik Mantan Narapidana dalam Putusan Mahkamah Konstitusi Nomor 4/PUU/VII/2009 dalam Perlindungan Konstitusi Hak Asasi Manusia - Suyitno Suyitno; Dudik Djaja Sidarta; Renda Aranggraeni (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study aims to examine the legal aspects of the restoration of political rights of former convicts in the Constitutional Court Decision Number 4/PUU/VII/2009, with a focus on the protection of human rights in the constitution. The decision is important in the context of changes in the law governing political rights for former convicts in Indonesia, which were previously limited by the existing legal system. In this decision, the Constitutional Court ruled that restrictions on political rights for former convicts were not in line with the principles of human rights guaranteed in the 1945 Constitution. This study uses a normative approach by analyzing laws and regulations, Constitutional Court decisions, and legal doctrines related to human rights and political rights. The results of the study indicate that the restoration of political rights for former convicts is an important step in ensuring the protection of human rights, as well as creating a more rehabilitative and inclusive criminal justice system. In addition, the decision also has important implications for efforts to improve the legal system in Indonesia, which should pay more attention to the rehabilitation of convicts and the restoration of their social status after serving their sentence.